2011
DOI: 10.1038/embor.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Mutability of prions

Abstract: Mutability of prionsPrions are shown to be mutable, and prion substrains have distinct mutation capacity. However, even clones that seem virtually immutable change when the environmental conditions are altered. Mutability is thus a prion substrain-specific attribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…In the experiments on the replication of 263K, HY, or SSLOW in dgPMCAb, we observed structural plasticity as reflected by the ability of the strains to change their PK resistance profile in response to different degrees of substrate glycosylation, while retaining molecular features responsible for the strain-specific phenotype. The concepts of phenotypic plasticity and norm of reaction can also be useful for explaining the reversible changes in strain characteristics upon altering the replication environment, for instance, when brain-derived prions are replicated in PMCA and then transferred back to animals (18,19,23) or replicated in cultured cells and then back into animals (2,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experiments on the replication of 263K, HY, or SSLOW in dgPMCAb, we observed structural plasticity as reflected by the ability of the strains to change their PK resistance profile in response to different degrees of substrate glycosylation, while retaining molecular features responsible for the strain-specific phenotype. The concepts of phenotypic plasticity and norm of reaction can also be useful for explaining the reversible changes in strain characteristics upon altering the replication environment, for instance, when brain-derived prions are replicated in PMCA and then transferred back to animals (18,19,23) or replicated in cultured cells and then back into animals (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Should we attribute vast phenotypic variations, for example those observed in cell lines (2,5), to actual strain mutations or to phenotypic plasticity due to replication in altered cellular environments? Is the term mutation applicable when someone deals with reversible or interconvertible changes between quasispecies or substrains?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, complete genetic ablation of Tau is fairly well tolerated in mice, suggesting that anti-Tau antibodies in the adult CNS are unlikely to meet safety concerns due to disruption of normal Tau physiology (68 -70). Finally, if parallels to prion disease hold true, there could be variable clinical responses in patients based on the conformation of the pathogenic species, and possibly evolution of protein aggregate structures away from a given therapy (71,72). Although the most important criterion will be the efficacy of an antibody in vivo, a strong understanding of the biology of the most effective agents will enable better selection and optimization.…”
Section: Antibodies To Target Pathologymentioning
confidence: 99%
“…Thus, when 22L prions were transferred from brain to PK1 cells, they gradually changed their properties, losing their ability to infect R33 cells and becoming sensitive to inhibition by swainsonine; these changes were reversed when the prions were returned to brain (15,16,18). We believe that prion populations are quasispecies (9, 10), consisting of a multitude of variants, the ones fittest for a particular environment predominating (4,15,21), and we have shown that variants arise in cloned prion populations in the course of propagation (15,16,18), explaining how quasispecies arise.…”
Section: Discussionmentioning
confidence: 99%